An Epistemological Look into "Concept" In Arabic: A Contrastive View - Mohammad, Ibrahim Kayed Mahmoud; Alanbar, Omar Abdullah; Bani-Khair, Baker; Al-Anbar, Khaled Abdullah; Al-Zyadat, Tareq Ibraheem (Technium Social Sciences Journal, 2023)
The paper mainly focuses on the term "concept" and "perception", as to know whether they mean the same, denote the same sign, and have the same meaning, or whether they differ in terms of significance and meaning. In this paper, we will try to compare them through their multiple definitions and their different uses in different sciences and disciplines of knowledge according to various theorists in the field. The "concept" and "perception" are two important terms in terminology, and despite this importance, scientists and researchers have not been able to define them clearly because they are connected with almost all areas of life and types of science, so the definitions continue to greatly vary, and the opinions of researchers differ on this matter, which made the argument difficult to point out direct differences between them historically and theoretically.